2021
DOI: 10.3390/w13070945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Sentinel-1A and Sentinel-2 in Small Waterbody Mapping over Urban and Mountainous Regions

Abstract: Accurate waterbody mapping can support water-related environment monitoring and resource management. The Sentinel series satellites provide high-quality Synthetic Aperture Radar (SAR) and optical observations that are commonly used in waterbody mapping. However, owing to the 10-m spatial resolution of Sentinel data, previous studies mostly focused on the mapping of large waterbodies. In this work, we evaluated the performance of small waterbody mapping over urban and mountainous regions with two datasets, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Previous studies have shown that the using watershed segmentation to extract waterbody has better mapping results than the single threshold method [1]. The watershed algorithm is a region extraction algorithm based on morphology, which grayscales the image and then uses the analysis of geographic morphology to segment the image gradient.…”
Section: Initial Waterbody Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the using watershed segmentation to extract waterbody has better mapping results than the single threshold method [1]. The watershed algorithm is a region extraction algorithm based on morphology, which grayscales the image and then uses the analysis of geographic morphology to segment the image gradient.…”
Section: Initial Waterbody Extractionmentioning
confidence: 99%
“…To this end, some studies propose to combine the above methods with change detection or time series analysis to determine the flooding range. However, practice has shown that flood extraction based on SAR images is susceptible to other confusing features such as shadows from mountains/buildings and flat surfaces [1]. Although many studies use reference data (such as DEM/NDVI) to remove noise, there are still many noises that cannot be removed, and it is easy to remove the correct waterbody.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of flood detection in VV polarization is higher than that in VH polarization [20], [21], so we selected the SAR images in VV polarization. The L2A products obtained by Sentinel-2 were processed to generate the modified normalized difference water index 3 > ID NUMBER < (MNDWI) [22] for validation. Fig.…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…Scientists have successfully applied remote sensing technologies in hydrogeological, environmental, and geological research using optical and radar data from various satellites: Sentinel-1 [1][2][3][4][5][6][7][8][9][10]; Sentinel-2 [2,3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]; Landsat-1, -2, and -3--8 [10,12,14,15,[21][22][23][24][25][26][27][28][29][30][31][32][33]; MODIS (Terra/Aqua) [24,[34][35][36][37][38][39][4...…”
Section: Introductionmentioning
confidence: 99%